Faktor-faktor Penentu Harga Tembaga di Pasar Internasional Terhadap PT. Freeport Indonesia - Pekey, Simon; Achsani, Noer Azam; Santoso, Moch. Hadi (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study aims to determine the factors that influence copper prices in the international market. The data used is monthly starting from January 2005 to December 2019. The variables are Copper price, Industrial Producer Index (IPI), Producer Price Index (PPI), Fed Rate, Consumer Price Index (CPI), New York Stock Exchange (NYSE), Oil Price, and Gold Price sourced from the internet. The research data was processed using the VECM method with Eviews 10 software. From data processing, the results were obtained: there is a two-way causality relationship between CPI and copper prices, gold prices and IPI have a one-way causality relationship to copper prices, and copper prices have a one-way causal relationship to PPI. The shock that occurred in the IPI variable gave the largest impulse response in the short and long term to the copper price in addition to the shock that occurred by the copper price itself. The shock was given by the fed rate, gold price, and CPI only gives an impulse response effect in the long term. In the short term, the largest decomposition variance was contributed by IPI and the price of copper itself, while in the long term the largest decomposition variance was contributed by IPI, fed rate, gold price, CPI, and also the price of copper itself. From the results of the study, it was concluded that IPI, Fed Rate, gold price, and CPI variables were the most influential factors in changes in copper prices. Keywords: causality, copper price, impulse response, variance Decomposition, VECM